REDESIGNING ISLAMIC TRANSFORMATIONAL LEADERSHIP FOR MUSLIM MINORITIES IN THE WEST - Fatimatuzzahro; Risanda (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Islam is a comprehensive religion that does not discuss one aspect of knowledge but covers all aspects, including leadership. Islamic leadership must be based on the pillars of Islam, namely the Qur'an and Hadith. Islamic leaders must work towards a vision to create a just society where the rule of law is upheld among all believers and non-believers. In the context of Islam in Western countries, leadership faced many challenges during the early years of the 21st century. These challenges can come from internal organizational challenges, such as social, cultural, and structural challenges. However, challenges arise from external contexts, such as social, cultural, legal, and political. In Islamic economic philosophy, the leadership model that is considered ideal is one based on fair and ethical leadership principles. This qualitative research aims to explain and redesign the transformational leadership theory with Islamic leadership. The study results are four characteristics that can influence transformational Islamic leadership: government pressure, media hostility, international politics, and a legal system. The impact of international politics unites the Muslim population to some extent. Australia's Muslim population hails from many countries, including a significant group born and raised in Australia. As a result, the Muslim population in Australia is a minority in an international context.